Compressive behaviour of child and adult cortical bone - Öhman, Caroline; Baleani, Massimiliano; Pani, Carla; Taddei, Fulvia; Alberghini, Marco; Viceconti, Marco; Manfrini, Marco (Bone (New York, N.Y.), 2011)
In this study, cortical bone tissue from children was investigated. It is extremely difficult to obtain human child tissue. Therefore, the only possibility was to use bone tissue, free from any lesion, collected from young bone cancer patients. The compressive mechanical behaviour of child bone tissue was compared to the behaviour of adult tissue. Moreover, two hypotheses were tested: 1) that the mechanical behaviour of both groups is correlated to ash density; 2) that yield strain is an invariant. Small parts of the diaphysis of femora or tibiae from 12 children (4–15years) and 12 adults (22–61years) were collected. Cylindrical specimens were extracted from the cortical wall along the longitudinal axis of the diaphysis. A total of 107 specimens underwent compressive testing (strain rate: 0.1s−1). Only the specimens showing a regular load–displacement curve (94) were considered valid and thereafter reduced to ash. It was found that the child bone tissue had significant lower compressive Young's modulus (−34%), yield stress (−38%), ultimate stress (−33%) and ash density (−17%) than the adult tissue. Conversely, higher compressive ultimate strain was found in the child group (+24%). Despite specimens extracted from both children and adults, ash density largely described the variation in tissue strength and stiffness (R2=in the range of 0.86–0.91). Furthermore, yield strain seemed to be roughly an invariant to subject age and tissue density. These results confirm that the mechanical properties of child cortical bone tissue are different from that of adult tissue. However, such differences are correlated to differences in tissue ash density. In fact, ash density was found to be a good predictor of strength and stiffness, also for cortical bone collected from children. Finally, the present findings support the hypothesis that compressive yield strain is an invariant. ► Compressive mechanical behaviour of child and adult cortical bone was investigated. ► Lower Young's modulus, yield and ultimate stress were found in child bone. ► Ash density correlated well with stiffness and strength also including child bone. ► Yield strain seems to be an invariant in both child and adult tissue.